Land tenure legislation and countryside education in Brazil - Elizabeth Moreira Gomes; Alexandre Fraga de Araújo; Maria Isabel Antunes-Rocha (Universidade Federal do Norte do Tocantins, 2019)
This paper aims at reflecting about two great questions concerning rural population; such questions constitute themselves as fundamental fighting pillars: land, and countryside education. Firstly, Brazil's Federal Constitution is taken under analyses, since it represents the official view towards rural population, secondly, reflections are drawn regarding what is suggested concerning Countryside Education. These reflections highlight the relationship between, what is here denominated as "invisibility" regarding rural population, and a movement towards an education that takes under consideration its specificities. The battles for better education for rural communities has guaranteed some achievements, thus making them visible, in detriment of a hegemonic view, which tends to take rural populations as part of a whole, disregarding their specificities and traditional knowledge.